1996
DOI: 10.1046/j.1365-3059.1996.d01-170.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ascochyta blight caused by Mycosphaerella pinodes on the translocation of carbohydrates and nitrogenous compounds from the leaf and hull to the seed of dried‐pea

Abstract: The effects of Ascochyta blight (caused by Mycosphaerella pinodes) on changes in dry weight and in water, carbohydrate, nitrogen and free amino acid contents were studied in the leaf, the hull and the seeds on the second fructifer node of pea (Pisum sativum). Pea plants were grown in a glasshouse and inoculated with various concentrations of conidia at the beginning of seed filling, with uninoculated plants as controls. Disease induced a premature water loss of hulls and leaves, accelerated seed desiccation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
25
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 20 publications
5
25
0
Order By: Relevance
“…The decline in foliar N in subplots where fungi were removed in the current experiment, particularly at low diversity, is consistent with past studies which have shown that foliar fungal diseases can cause N retention in diseased leaves (Bastiaans ; Garry et al . ; Gooding et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…The decline in foliar N in subplots where fungi were removed in the current experiment, particularly at low diversity, is consistent with past studies which have shown that foliar fungal diseases can cause N retention in diseased leaves (Bastiaans ; Garry et al . ; Gooding et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, most of the cultivars that had some form of tissue-specific resistance were late-maturing. Mycosphaerella blight can cause a rapid senescence of infected tissue, which speeds up plant maturation (Garry et al 1996). However, all of the early-maturing finished flowering before the late-maturing lines, so early maturity appears to be a characteristic of these cultivars rather than a consequence of severe mycosphaerella blight development.…”
Section: Discussionmentioning
confidence: 99%
“…However, another field study demonstrated that severe disease development at any stage from the start of flowering to pod formation resulted in reductions in seed weight (Xue et al 1997). The formation of brown to purple mycosphaerella blight lesions on the leaves and stem diminishes photosynthesis, which leads to reduced starch accumulation in the seeds (Garry et al 1996). Repeated applications of foliar fungicides will reduce mycosphaerella blight severity, but this is not cost-effective (Xue et al 1997;Wang et al 2000;Xue and Warkentin 2001;Xue et al 2003).…”
mentioning
confidence: 99%
“…Severe occurrence of mycosphaerella blight causes spots on leaves, stems, and pods, foot rot, reduced seed size, and a reduced number of seeds per stem (Lawyer, 1984;Tivoli et al, 1996). Diminished photosynthetic area due to lesion formation on leaves and stems results in decreased accumulation of starch in seeds (Garry et al, 1996). Grain yield instability due to insuffi cient disease resistance has reduced farmers' confi dence in cultivating fi eld pea (Wroth, 1998a).…”
mentioning
confidence: 99%